2022
DOI: 10.1186/s12989-022-00488-5
|View full text |Cite
|
Sign up to set email alerts
|

Road tunnel-derived coarse, fine and ultrafine particulate matter: physical and chemical characterization and pro-inflammatory responses in human bronchial epithelial cells

Abstract: Background Traffic particulate matter (PM) comprises a mixture of particles from fuel combustion and wear of road pavement, tires and brakes. In countries with low winter temperatures the relative contribution of mineral-rich PM from road abrasion may be especially high due to use of studded tires during winter season. The aim of the present study was to sample and characterize size-fractioned PM from two road tunnels paved with different stone materials in the asphalt, and to compare the pro-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 93 publications
5
13
0
Order By: Relevance
“…PMs can be categorized into three modes, which include coarse particles (diameter between 2.5 and 10 µm), fine particles (with a diameter between 0.1 to 2.5 µm), and ultrafine particles (diameters ≤ 0.1 µm or 100 nm) [4,5]. The coarse category is primarily generated from attrition processes, namely, mechanical abrasion, the re-suspension of road and soil dust, volcanic eruptions, and sea spray [6]. On the other hand, fine and ultrafine mode particles evolve mainly from combustion processes, e.g., biomass burning, motor vehicle exhaust, coal combustion, and chemical processes in the atmosphere [7,8].…”
Section: Introduction Of Impact Of Pm 01mentioning
confidence: 99%
“…PMs can be categorized into three modes, which include coarse particles (diameter between 2.5 and 10 µm), fine particles (with a diameter between 0.1 to 2.5 µm), and ultrafine particles (diameters ≤ 0.1 µm or 100 nm) [4,5]. The coarse category is primarily generated from attrition processes, namely, mechanical abrasion, the re-suspension of road and soil dust, volcanic eruptions, and sea spray [6]. On the other hand, fine and ultrafine mode particles evolve mainly from combustion processes, e.g., biomass burning, motor vehicle exhaust, coal combustion, and chemical processes in the atmosphere [7,8].…”
Section: Introduction Of Impact Of Pm 01mentioning
confidence: 99%
“…Nevertheless, traffic emissions remain a major source of increased urban air PAH levels. Recent studies of road tunnels PM suggested that PAHs on traffic PM 2.5 were primarily attached to aggregates of ultrafine PM originating from the combustion of transportation fuel [ 53 , 54 ]. More US EPA PAHs have been found in the ultrafine and fine PM (PM 2.5 ) samples than in the coarse PM, which to a large degree seem to originate from non-combustion sources such as bitumen and tires [ 54 ].…”
Section: Pm 25 Sources and Pah Characteristicsmentioning
confidence: 99%
“…Epidemiological studies indicate that short-term exposure to both coarse and fine PM is associated with respiratory hospital admissions and mortality [ 17 , 18 ]. Furthermore, some animal studies [ 19 ] and in vitro experiments have reported higher pro-inflammatory responses of coarse than fine PM [ 19 26 ], whereas other animal studies [ 27 , 28 ] and in vitro studies [ 29 31 ] show similar or higher responses for the fine than coarse PM. The relative impact of coarse versus fine and ultrafine PM depends on their specific sources, but also on the model system and health outcome examined.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that particles derived from different stone (rock) aggregates used in road pavement may induce inflammatory responses of different magnitude [ 11 , 38 40 ], suggesting that the choice of stone type may be of importance for adverse respiratory effects induced by traffic-related PM. In our recent study, particles of different sizes were sampled inside two road tunnels paved with different stone materials [ 29 ]. The results showed that fine PM (PM 2.5-0.18 ) induced higher pro-inflammatory responses in human bronchial epithelial cells (HBEC3-KT cells) than coarse PM (PM 10-2.5 ), whereas the potency of the ultrafine PM (< PM 0.18 ) was more variable.…”
Section: Introductionmentioning
confidence: 99%